Principles of Listening in The Quran and Their Development in Islamic Preaching: A Study of Surah Al-Nahl/16:78 - Fauziah, Mira (Jurnal Ilmiah Al-Mu'ashirah: Media Kajian Al-Qur'an dan Al-Hadits Multi Perspektif, 2023)
The Quran mentions that humans are endowed with a sense of hearing, yet they fail to utilize it to listen to the verses and guidance of Allah. This work aims to examine the principles of listening in the Quran and their development in Islamic preaching. This study employs content analysis to comprehend the significance of hearing Surah Al-Nahl/16:78. The research findings reveal that through the utilization of the sense of hearing, individuals acquire knowledge, leading them to obey all of Allah's commands and prohibitions. The sense of hearing is highly effective when employed to listen to preaching materials via videos on various social media platforms.